2014
DOI: 10.1007/s12350-014-9983-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of post-exercise stunning by early gated SPECT myocardial perfusion imaging: Results from the IAEA multi-center study

Abstract: Early post-exercise imaging is feasible, and can potentially improve the detection of post-ischemic stunning without compromising image quality and perfusion data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…20 -22 Moreover, LV volume and EF values were also influenced by the delay from tracer injection to images acquisition, when correlated to the amount of ischemia. 23 In the study by Mut et al in the SD protocol group the rest evaluation was performed first, thus the possible effect of a prolonged stunning also affecting rest evaluation was not an issue. 23 In conventional SD protocol, however, stress study is usually performed first, to allow for the possibility of a stress-only approach in the case of normal perfusion and function, thus requiring one tracer injection only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 -22 Moreover, LV volume and EF values were also influenced by the delay from tracer injection to images acquisition, when correlated to the amount of ischemia. 23 In the study by Mut et al in the SD protocol group the rest evaluation was performed first, thus the possible effect of a prolonged stunning also affecting rest evaluation was not an issue. 23 In conventional SD protocol, however, stress study is usually performed first, to allow for the possibility of a stress-only approach in the case of normal perfusion and function, thus requiring one tracer injection only.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the study by Mut et al in the SD protocol group the rest evaluation was performed first, thus the possible effect of a prolonged stunning also affecting rest evaluation was not an issue. 23 In conventional SD protocol, however, stress study is usually performed first, to allow for the possibility of a stress-only approach in the case of normal perfusion and function, thus requiring one tracer injection only. In our study, rest study in the SD protocol was performed on average 3 h after stress study and the possibility of a prolonged stunning in patients with severe ischemia, affecting rest LVEF, may explain the underestimation of the change in LVEF when compared to the DD protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors concluded that ''early post-exercise imaging is feasible, and can potentially improve the detection of post-ischemic stunning without compromising image quality and perfusion data''. 18 In another recent study, Brodov et al 19 performed serial 2-minutes acquisitions postregadenoson injection with a high-efficiency solid-state CZT SPECT camera in 50 patients. They showed that myocardial stunning (i.e., negative LVEF reserve) was detectable in patients with myocardial ischemia only in early acquisitions (images obtained at the 5th and 9th minutes).…”
mentioning
confidence: 99%
“…5 Its early detection using a conventional Anger-camera is limited by several technologically inherent pitfalls: First, the need to wait for at least 15 minutes, and sometimes up to 60 minutes following a radiotracer injection before initiating image acquisition because of hepatic uptake; 6,7 second, acquisition time itself is very long, frequently more than ten minutes, allowing partial recovery of the LV function during the acquisition itself. Thus, acquiring images at peak stress or very early post-stress using a conventional camera is unfeasible.…”
mentioning
confidence: 99%